2018
DOI: 10.7224/1537-2073.2017-035
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Effect of Antigravity Treadmill Training on Muscle Oxidative Capacity, Muscle Endurance, and Walking Function in a Person with Multiple Sclerosis

Abstract: Muscle oxidative capacity and muscle endurance, as well as walking function, improved in a person with MS after training on an antigravity treadmill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We chose to use accelerometer-based mechanomyography (aMMG) to evaluate muscle endurance [ 13 ]. This approach has been used successfully on limb muscles [ 18 , 19 ] and muscles in the upper back [ 16 ]. Studies of the lower back muscles have reported changes in surface muscle electromyography signals and force development as indices of fatigue/endurance [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…We chose to use accelerometer-based mechanomyography (aMMG) to evaluate muscle endurance [ 13 ]. This approach has been used successfully on limb muscles [ 18 , 19 ] and muscles in the upper back [ 16 ]. Studies of the lower back muscles have reported changes in surface muscle electromyography signals and force development as indices of fatigue/endurance [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…We showed that patients with high levels of disability were able to complete GXT in 10 out of 25 occasions (40% success rate) and 50% of our participants achieved 90% of their age-predicted maximal heart rates during GXT, potentially important information needed for planning of future studies among patients with high levels of MS-related disability [26,78,82,84,85,[87][88][89][90][91][92]. We found that our participants with high disability achieved 12.2% greater maximal workload during GXT as a result of training, despite small increases in maximal heart rate (1.8%), maximal respiratory exchange ratio (2.2%), and maximal V O 2 (6.6%).…”
Section: Ability To Perform Gxt and Improvements In Cardiorespiratorymentioning
confidence: 69%
“…We showed that patients with high levels of disability were able to complete GXT in 10 out of 25 occasions (40% success rate) and 50% of our participants achieved 90% of their age-predicted maximal heart rates during GXT, potentially important information needed for planning of future studies among patients with high levels of MS-related disability (26,78,85,86,(88)(89)(90)(91)(92)(93)(94). We found that our participants with high disability achieved 12.2% greater maximal workload during GXT as a result of training, despite small increases in maximal heart rate (1.8%), maximal respiratory exchange ratio (2.2%), and maximal VȮ 2 (6.6%).…”
Section: Ability To Perform Gxt and Improvements In Cardiorespiratory Reservementioning
confidence: 69%